Research on the Financing Sources of Start-Ups: A Case Study of Poland - Wojciech LEWICKI (Communications of International Proceedings, 2020)
In today's market reality, nobody doubts that financing the activities of enterprises is a complex process influenced by many factors. It is obvious that a market entity with several years of experience and an established market position has different opportunities to raise capital, and a start-up that bases its strategy solely on assumptions that a given product will find its buyers in the future. The article presents selected research results on the sources of financing startups in Poland. The aim of the research was to gain extensive knowledge on the methods of raising capital by these entities. In particular, identification of business models, types of selected financing sources, determination of current needs and indication of barriers to obtaining funds. This research may contribute to the development of universal solutions in the field of financing startup activities especially in Central European countries. The presented and interpreted results can be the basis and incentive for further research on the topic related to the development of entrepreneurship and startup ecosystems, both at the local and global level.
Keywords: Start-Ups; Financing; Entrepreneurship.